Differential RPA-1 and RAD-51 recruitment in vivo throughout the C. elegans germline, as revealed by laser microirradiation. Issue 2 (13th December 2017) - Koury, Emily; Harrell, Kailey; Smolikove, Sarit
Abstract: Studies of the repair pathways associated with DNA double strand breaks (DSBs) are numerous, and provide evidence for cell-cycle specific regulation of homologous recombination (HR) by the regulation of its associated proteins. Laser microirradiation is a well-established method to examine in vitro kinetics of repair and allows for live-imaging of DSB repair from the moment of induction. Here we apply this method to whole, live organisms, introducing an effective system to analyze exogenous, microirradiation-induced breaks in the Caenorhabditis elegans germline. Through this method we observed the sequential kinetics of the recruitment of ssDNA binding proteins RPA-1 and RAD-51 in vivo . We analyze these kinetics throughout different regions of the germline, and thus throughout a range of developmental stages of mitotic and meiotic nuclei. Our analysis demonstrates a largely conserved timing of recruitment of ssDNA binding proteins to DSBs throughout the germline, with a delay of RAD-51 recruitment at mid-pachytene nuclei. Microirradiated nuclei are viable and undergo a slow kinetics of resolution. We observe RPA-1 and RAD-51 colocalization for hours post-microirradiation throughout the germline, suggesting that there are mixed RPA-1/RAD-51 filaments. Finally, through live imaging analysis we observed RAD-51 foci movement with low frequency of coalescence.